2006
DOI: 10.1158/0008-5472.can-06-0453
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Epidermal Growth Factor Receptor Somatic Mutant Proteins Shows Increased Sensitivity to the Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor, Erlotinib

Abstract: We show that two commonly occurring epidermal growth factor receptor (EGFR) somatic mutations, L858R and an in-frame deletion mutant, Del(746-750), exhibit distinct enzymatic properties relative to wild-type EGFR and are differentially sensitive to erlotinib. Kinetic analysis of the purified intracellular domains of EGFR L858R and EGFR Del(746-750) reveals that both mutants are active but exhibit a higher K M for ATP and a lower K i for erlotinib relative to wild-type receptor. When expressed in NR6 cells, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
303
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(320 citation statements)
references
References 45 publications
10
303
0
1
Order By: Relevance
“…In this study, pathologic N status (N1 or N2) or pathologic stage (stage II or III) were determined to not be statistically informative prognostic factors for DFS using multivariate analysis (HR 1.71; P=0.353, or HR 0.75; P=0.627, respectively). Additionally, patients with Ex21 tumors (12). This data might support the results and hypothesis of Isaka's study.…”
supporting
confidence: 88%
“…In this study, pathologic N status (N1 or N2) or pathologic stage (stage II or III) were determined to not be statistically informative prognostic factors for DFS using multivariate analysis (HR 1.71; P=0.353, or HR 0.75; P=0.627, respectively). Additionally, patients with Ex21 tumors (12). This data might support the results and hypothesis of Isaka's study.…”
supporting
confidence: 88%
“…A European phase III randomized controlled trial of erlotinib (Tarceva ® ) vs. chemotherapy (EURTAC trial) demonstrated that NSCLC patients with exon 19 deletion have a more favorable response rate, PFS and OS compared with patients with exon 21 L858R mutation (9). Based on in vitro cell cultures, another study demonstrated that exon 19 deletion may have a greater affinity for TKIs and display a higher sensitivity to treatment compared with exon 21 L858R mutation (15). However, a retrospective clinical study by Igawa et al (10) revealed no significant differences in RR, PFR or OS between patients with exon 19 deletion and those with exon 21 L858R mutation after receiving gefitinib, which is consistent with the stratification analysis results of another two large, randomized, phase III trials [NEJ002 (12) and WJTOG3405 (13)].…”
Section: Discussionmentioning
confidence: 99%
“…We did not include IPASS [18] or First-SIGNAL [19] trials because both trials mainly enrolled never-smokers, the analysis of the EGFRm subgroup was retrospective, and a significant amount of Finally, this meta-analysis also demonstrates that EGFR TKI is significantly more effective in conferring PFS benefit against exon 19 deletion than against L858R substitution when compared with platinum-doublet chemotherapy. In vitro data have demonstrated that gefitinib and erlotinib both have a higher affinity for the exon 19 deletion than L858R mutation [20], resulting in inhibition of the kinase activity of mutated exon 19 deletion EGFR much faster and tighter with both EGFR TKIs [21]. As early as in 2006, clinical observations have reported that exon 19 deletion seems to derive longer PFS from EGFR TKI than L858R substitution [22,23].…”
Section: Discussionmentioning
confidence: 99%